Internalization of Muhammadiyah Life Values in the development of science and technology in the era of Industry 5.0: (Integration, internalization, role, contribution, and challenges) - Yogi Sopian Haris; Muhammad Lailan Arqam; Abdul Hafiz (Priviet Social Sciences Journal, 2025)
Industrial Revolution 5.0 brings significant disruption in the field of science and technology, but at the same time, it presents new challenges related to the need for integration between technological advancement and humanitarian, spiritual, and Islamic values. The main issue in this research is the weak integration of Islamic values, particularly the values of Muhammadiyah's way of life, in the development of science and technology in that era. The objective of this research is to integrate Muhammadiyah’s life values, such as monotheism, enjoining good and forbidding wrong, noble character, respect for human dignity, and brotherhood, into the development of science and technology, as well as to analyze the role, contribution, and challenges of Muhammadiyah in this integration process. This study used a library research method with a qualitative approach. Data were collected from various primary and secondary authoritative literature sources. The data analysis techniques used were content, thematic, and critical analyses. The research results show that internalization is carried out by integrating the values of Muhammadiyah's way of life with science, technology, and Islamic values as a strategic foundation for addressing the challenges of the times. Through an integrative epistemological approach (bayani, burhani, and irfani) and the spirit of tajdid, Muhammadiyah has developed various innovations such as integrative education, digital preaching, environmentally friendly technology, big data-based management, computer and air conditioning innovations named ITMU (Innovationn Technology of Muhammadiyah), and the latest innovation, the Global Unified Hijri Calendar. Despite facing challenges such as the dichotomy of knowledge, resistance to change, concerns about losing traditional values, and the dominance of secular epistemology, Muhammadiyah remains committed to building a just, sustainable civilization rooted in divine values.